Advancing biomedical applications: an in-depth analysis of silver nanoparticles in antimicrobial, anticancer, and wound healing roles - Jangid, Himanshu; Singh, Sudhakar; Kashyap, Piyush; Singh, Avtar; Kumar, Gaurav (Frontiers in Pharmacology, 2024)
Introduction: Silver nanoparticles (AgNPs) have gained significant attention in biomedical applications due to their unique physicochemical properties. This review focuses on the roles of AgNPs in antimicrobial activity, anticancer therapy, and wound healing, highlighting their potential to address critical health challenges. Methods: A bibliometric analysis was conducted using publications from the Scopus database, covering research from 2002 to 2024. The study included keyword frequency, citation patterns, and authorship networks. Data was curated with Zotero and analyzed using Bibliometrix R and VOSviewer for network visualizations. Results: The study revealed an increasing trend in research on AgNPs, particularly in antimicrobial applications, leading to 8,668 publications. Anticancer and wound healing applications followed, with significant contributions from India and China. The analysis showed a growing focus on “green synthesis” methods, highlighting a shift towards sustainable production. Key findings indicated the effectiveness of AgNPs in combating multidrug-resistant bacteria, inducing apoptosis in cancer cells, and promoting tissue regeneration in wound healing. Discussion: The widespread research and applications of AgNPs underscore their versatility in medical interventions. The study emphasizes the need for sustainable synthesis methods and highlights the potential risks, such as long-term toxicity and environmental impacts. Future research should focus on optimizing AgNP formulations for clinical use and further understanding their mechanisms of action. Conclusion: AgNPs play a pivotal role in modern medicine, particularly in addressing antimicrobial resistance, cancer treatment, and wound management. Ongoing research and international collaboration are crucial for advancing the safe and effective use of AgNPs in healthcare.